Penerapan Metode Certainty Factor untuk Sistem Pakar Diagnosa Penyakit Degeneratif - Abdul Malik Buna; Citra Yustitya Gobel (STMIK Budi Darma, 2023)
Degenerative disease is a health condition in which organs or tissues related to the human condition continue to decline over time. This disease occurs due to changes in the body's cells which ultimately affect organ function as a whole. The current problem is the lack of public knowledge of the symptoms and types of degenerative diseases as well as the awareness to check health conditions because it is hampered by the relatively expensive cost of examinations. The purpose of this research is to design an expert system for diagnosing degenerative diseases using the Certainty Factor method so that it can make it easier for people to diagnose degenerative diseases. The research method used is the Research and Development method where the data sources used are primary and secondary data with data collection methods through observation and interviews. Research applies the certainty factor method to the diagnosis of two regenerative diseases, namely stroke and coronary heart disease, the results obtained from the calculation of the certainty factor method based on the MB weight of each disease symptom and conducting trials on three patients have obtained a CF percentage value above 90% having symptoms of Stoke disease while the results of the expert system implementation are designed on a mobile platform so that users can easily consult disease diagnoses